Poverty in South Africa: an analysis of former vs non-former homeland areas - Masenya, Lesego (My University, 2019)
The objective of the study is to analyse the effect former homeland status on poverty in South Africa. The study uses 2011 Census community profiles data from Statistics South Africa and cartographic data. Two methodologies are used in order to identify the effect of former homeland status on poverty, i.e., Ordinary Least Squares (OLS) and Regression Discontinuity Design (RDD). Notably, the RDD model is the main model as it formally identifies the treatment effect by comparing former and non-former homelands within a quasi-experimental framework. The results indicate that former homeland areas experience higher poverty levels relative to non-former homeland areas. The analysis shows that a large portion of the “raw” poverty differential is explained by differences in observed characteristics between former and non-former homeland areas. The remaining difference is attributable to former homeland status. The ‘scarring effect’ is small but statistically significant. Thus, the results call for government intervention aimed at reducing differences in observed characteristics of former and non-former homeland areas. The study notes that such mechanisms will narrow the difference in poverty rates but might not close it entirely since part of the difference is structural and depends on the rate at which the ‘scarring effect’ fades overtime.
A Research Report submitted in partial fulfilment of the Degree of Master of Economic Science in the School of Economic and Business Sciences, University of the Witwatersrand
Keywords: Migrant labor--South Africa--History; Homelands (South Africa)--Economic conditions